2020
DOI: 10.1186/s13014-020-01630-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose cone-beam CT (LD-CBCT) reconstruction for image-guided radiation therapy (IGRT) by three-dimensional dual-dictionary learning

Abstract: Background: To develop a low-dose cone beam CT (LD-CBCT) reconstruction method named simultaneous algebraic reconstruction technique and dual-dictionary learning (SART-DDL) joint algorithm for image guided radiation therapy (IGRT) and evaluate its imaging quality and clinical application ability. Methods: In this retrospective study, 62 CBCT image sets from February 2018 to July 2018 at west china hospital were randomly collected from 42 head and neck patients (mean [standard deviation] age, 49.7 [11.4] years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Previous study indicated that daily CBCT scan for IGRT could increase the secondary cancer risk by 2% up to 4% [ 6 ]. To reduce the additional dose for patients generated from IGRT, the researchers have proposed several low-dose CBCT imaging technologies [ 7 , 8 ]. Now, the low-dose protocols of CBCT scanning have been widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study indicated that daily CBCT scan for IGRT could increase the secondary cancer risk by 2% up to 4% [ 6 ]. To reduce the additional dose for patients generated from IGRT, the researchers have proposed several low-dose CBCT imaging technologies [ 7 , 8 ]. Now, the low-dose protocols of CBCT scanning have been widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a scale ratio similar to the clinically acceptable PNSR (36.36) of low-dose CBCT, 9 0.1-unit intervals between compression ratios of 2 and 3 were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…After 2015, the number of publications is increased significantly. There are 9 publications in 2016 [118][119][120][121][122][123][124][125][126], 7 publications in 2017 [127][128][129][130][131][132][133], 10 publications in 2018 [134][135][136][137][138][139][140][141][142][143], 9 publications in 2019 [144][145][146][147][148][149][150][151][152] and 8 publications in 2020 [153][154][155][156][157][158][159][160]. Within the subspecialty of radiation therapy, the numbers of publications in the fields of clinical implementation, plan optimization, plan evaluation and quality assurance are 23 papers (37%), 16 papers (26%), 14 papers (23%) and 9 papers (14%), respectively.…”
Section: Scientific Researchmentioning
confidence: 99%